Operating Systems Usability: A Comparative Study - Urbano Patayon; Nerico Mingoc (Philippine Association of Institutions for Research, Inc., 2019)
As usability testing becomes more popular and widely recognized, operating systems' users are still relying on reviews that are based on the price, standard feature and satisfaction survey as to which product will be patronized. Measuring usability requires assessment on three product attributes or factors namely: effectiveness, efficiency, and user satisfaction. There are thirty-seven (37) respondents used in the study. Each respondent is required to perform the given task in each version of the Windows operating system. Time to complete the task and behavioral manifestations were recorded. Based on the data gathered and analyzed, results show that Windows 10 has the most number of the task with the highest completion rate in comparison with two operating systems in the study. Regarding efficiency, Windows 8 has the highest average task completion time. As to user satisfaction, the majority of the respondents were frustrated in the different task under Windows 8 while most of them are delighted in the tasks under Windows 7. Regarding engagement and boredom, the result reveals that users are engaged at the same time felt bored on tasks under Windows 10.